Sleeping with Herodotus in The English Patient - Provencal, Vernon (Studies in Canadian Literature / Études en littérature canadienne, 2002)
Michael Ondaatje's narratological view of history places him in the proximity of postcolonial/postmodern historicism that treats "history" as "text." But while The English Patient offers a postcolonial/postmodern critique of The Histories, Herodotus cannot simply be dismissed; he is literally bound up with the English patient's life. Ondaatje bifurcates Herodotus into main and supplemental arguments, corresponding to imperial and existential histories — a bifurcation that does not exist in The Histories. Such an interpretation is a result of Ondaatje's ongoing reflection on the "text" of Western history in light of its postcolonial/postmodern deconstruction.